Proceedings of the second annual meeting of GenE-HumDi (COST Action 21113) - Ortiz-Bueno, María; Ramos-Hernández, Iris; Algeciras-Jiménez, Luis; Kalter, Nechama; Rodríguez-Madoz, Juan Roberto; Bonafont, Jose; Nair, Rajeevkumar Raveendran; Feeney, Oliver; Torella, Laura; Montoliu, Lluis; Patsali, Petros; Mussolino, Claudio; et al. (Frontiers in Genome Editing, 2025)
Genome editing for the treatment of human disease (GenE-HumDi) is an EU-funded COST Action for the development and consolidation of academic, industrial and healthcare feedback networks aiming to accelerate, foster and harmonize the approval of genome-editing (GE) therapies. GenE-HumDi offers mobility grants, supports educational courses, and hosts conferences and meetings to promote synergistic interactions among and across partners active in the discovery, validation, optimization, manufacturing and clinical application of genomic medicines. Furthermore, it provides young and early career scientists with a supportive and world-class environment to foster networking and international collaborations within the GE field. We compiled the proceedings of the second Annual GenE-HumDi Meeting held in Limassol, Cyprus, in 2024. Over three days, renowned experts from the field updated an audience of over 70 GenE-HumDi members and non-member scientists on the latest discoveries and ongoing projects, discussed the status of the field, and identified GenE-HumDi action priorities to advance research and development for GE medicines. Seven focused discussion groups identified gaps in knowledge, standardization and dissemination for new GE tools, delivery methods, safety monitoring, validation for clinical use, and progress in industrial manufacturing and regulatory issues. Simultaneously, publicity about the event itself contributed to outreach and dissemination of GE for human diseases. Therefore, the conclusions of that meeting, summarized here, serve as a compass toward GE application in Europe through coordination, enhanced collaboration and focus on critical developments.